Transcriptome of airway neutrophils reveals an interferon response in life-threatening respiratory syncytial virus infection - Besteman, Sjanna B.; Callaghan, Amie; Langedijk, Annefleur C.; Hennus, Marije P.; Meyaard, Linde; Mokry, Michal; Bont, Louis J.; Calis, Jorg J.A. (Clinical immunology (Orlando, Fla.), 2020)
Neutrophils are the most abundant cell type infiltrating the airways during severe respiratory syncytial virus (RSV) infection. Their exact role in disease pathophysiology remains enigmatic. Therefore, we determined genome-wide RNA expression profiles of local and systemic neutrophils in RSV bronchiolitis to provide further insight into local neutrophil biology. We performed a single-center analysis, in 16 infants, admitted to the pediatric intensive care unit with severe RSV bronchiolitis. Neutrophils were isolated from blood and tracheobronchial aspirates (sputum). After low input RNA sequencing, differential expression of genes was determined followed by gene set analysis. Paired transcriptomic analysis of airway versus blood neutrophils showed an inflammatory phenotype, characterized by NF-kB signaling and upregulated expression of IL-6 and interferon pathways. We observed distinct expression of neutrophil activation genes (TNFSF13B, FCER1G). Our data indicate that airway neutrophils regulate their function at the transcriptional level in response to viral infection. It also suggests that local interferon drives the neutrophil response of severe RSV bronchiolitis.